2015
DOI: 10.1364/ol.40.004799
|View full text |Cite
|
Sign up to set email alerts
|

Irradiance enhancement and increased laser damage threshold in As_2S_3 moth-eye antireflective structures

Abstract: It has been experimentally observed that moth-eye antireflective microstructures at the end of As2S3 fibers have an increased laser damage threshold relative to thin-film antireflective coatings. In this work, we computationally study the irradiance enhancement in As2S3 moth-eye antireflective microstructures in order to explain the increased damage threshold. We show that the irradiance enhancement occurs mostly on the air side of the interfaces and is minimal in the As2S3 material. We give a physical explana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Further refinements are currently under investigation, including reduction of optical losses via methods such as polishing the fiber end faces, applying an antireflective coating to the fiber end faces, and cladding the fiber core in a core/clad architecture for more-efficient waveguiding. 26 With such improvements, the fibers would be suitable for delivery of visible and infrared light for a host of applications including illumination for medical diagnostics, surgical assisting, and chemical/biological sensing. With ORMOCHALC fibers being potentially antibacterial 27 and antimicrobial, 28 they present an advantage in comparison to chalcogenide glass fibers, which are typically unsuitable for medical applications, because they often contain toxic components, such as arsenic.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further refinements are currently under investigation, including reduction of optical losses via methods such as polishing the fiber end faces, applying an antireflective coating to the fiber end faces, and cladding the fiber core in a core/clad architecture for more-efficient waveguiding. 26 With such improvements, the fibers would be suitable for delivery of visible and infrared light for a host of applications including illumination for medical diagnostics, surgical assisting, and chemical/biological sensing. With ORMOCHALC fibers being potentially antibacterial 27 and antimicrobial, 28 they present an advantage in comparison to chalcogenide glass fibers, which are typically unsuitable for medical applications, because they often contain toxic components, such as arsenic.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The resulting ORMOCHALC optical fibers were used in a waveguiding demonstration, which showed that 27% of the IR power inputted was successfully guided through the ORMOCHALC fiber to the detector. Further refinements are currently under investigation, including reduction of optical losses via methods such as polishing the fiber end faces, applying an antireflective coating to the fiber end faces, and cladding the fiber core in a core/clad architecture for more-efficient waveguiding . With such improvements, the fibers would be suitable for delivery of visible and infrared light for a host of applications including illumination for medical diagnostics, surgical assisting, and chemical/biological sensing.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 . In addition, it has a higher LIDT 6,17 compared to ARCs and does not depend on the adhesion of the optical surface. This enables the utilization of ARMs in high-energy optical systems, even with materials that are not suitable for proper polishing or have issues with adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the emission of the nanobody that is emitted from the single molecule can be applied to influence the DNA structure without using any addition to the fluorescent markers [55]. Thus, it is important to know how to match the fluorescent properties of the NPs with the detected molecule and consequently to improve the selectivity of the detection [26].Different plasmonic nanostructures, such as gold and silver formed as nanorod, spheroid, sphere, ellipsoid, and half ellipsoid (moth-eye) lead to enhance the electric field around them to the surrounding medium which improves the optical coupling of any fluorescent emission matched with surface plasmonic resonance (SPR) wavelength [56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%